Cross-shore transport in a daily varying upwelling regime: A case study of barnacle larvae on the southwestern Iberian coast - Trindade, A. (2019)
With favored offshore and downstream advection, the question of which physical mechanism may promote onshore transport of larvae in upwelling systems is of central interest. We have conducted a semi-realistic high resolution (0.25 km) numerical study of Lagrangian transports across the inner-shelf under upwelling-favorable wind forcing conditions, focusing on the shelf area of the Southwestern Portuguese coast, in the lee of Cape Sines. We add our findings to several years of biological observations of C. montagui, a planktonic species with higher recruitment during the upwelling peak timely with the daylight flood. Simulations cover a fifteen days period during the summer of 2006. We focused on Spring and Neap tide periods and observed upfront differences between simulations and the in situ observations. However, the model is capable of representing the main dynamics of the region, namely the repetitive character of the inner-shelf currents. We find that the cross-shore flow varies significantly in the daily cycle, and locally within a scale of a few kilometers in association with local topography and the presence of the cape. We consider the region immediately in the lee of the cape to be an upwelling shadow where the larvae became retained, and found that tidally tied migration proves beneficial for successful recruitment during the spring tides period. Our work suggested that the wind is not the only mechanism responsible for the daily variability of the cross-shore exchange. However, its sharp reversal at midday is critical for the advection of larvae towards the coast.